TSH and TPOAB as predictors of thyroid disease in diabetic patients - Bedone, Raquel V. [UNESP]; Pimenta, Walkyria P. [UNESP]; Carvalho, Lidia R. [UNESP]; Mazeto, Gláucia Maria Ferreira da Silva [UNESP] (Lippincott Williams & Wilkins, 2008)
We tested the values of antithyroid peroxidase antibody and thyrotropin levels for the development of thyroid dysfunction in 109 diabetic patients. Baseline thyrotropin level was a predictor of thyroid dysfunction in diabetic patients, excluding nodular disease. The antithyroid peroxidase antibody had no predictive value for thyroid dysfunction.
Keywords: TSH; TPOAB; thyroid dysfunction; diabetes mellitus; predictors